Clash of Kings – A Regional Security Perspective in “Songs of Ice and Fire” - Vujinović, Nikola (Journal of Regional Security, 2018)
Review of George R.R. Martin. 2011. A Song of Ice and Fire, books 1-5. New York: Bantam Books.